2008
DOI: 10.1161/circulationaha.107.748772
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Intervention for Prevention of Left Ventricular Remodeling and Improving Prognosis in Myocardial Infarction

Abstract: Early reperfusion of totally occluded coronary arteries with thrombolysis and/or percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI) reduces infarct size, cardiac mortality, and in-hospital events. 1,2 Prompt reperfusion of epicardial blood flow reduces infarct size and mortality rates, in-hospital events, and reinfarction. Furthermore, successful reperfusion greatly affects the reduction in infarct size and left ventricular (LV) function. The reduction in infarct size and the improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 139 publications
1
16
0
Order By: Relevance
“…Furthermore, ANP activates reperfusion injury salvage kinase, which has been shown to mediate ischemic preconditioning and postconditioning. In several studies with a reperfusion model in vivo , ANP showed inhibition of the occurrence of reperfusion arrhythmia, preservation of ATP content in the ischemic myocardium, and inhibition of neutrophil-induced endothelial cytotoxity (48). …”
Section: Cardioprotective Action Of Otmentioning
confidence: 99%
“…Furthermore, ANP activates reperfusion injury salvage kinase, which has been shown to mediate ischemic preconditioning and postconditioning. In several studies with a reperfusion model in vivo , ANP showed inhibition of the occurrence of reperfusion arrhythmia, preservation of ATP content in the ischemic myocardium, and inhibition of neutrophil-induced endothelial cytotoxity (48). …”
Section: Cardioprotective Action Of Otmentioning
confidence: 99%
“…Ventricular remodeling may continue for weeks or months until the distending forces are counterbalanced by the tensile strength of the collagen scar; this balance then determines the size, location, and transmurality of the infarct, the extent of myocardial stunning, ventricular loading conditions, and local trophic factors [143]. Although contemporary treatment attenuates remodeling [144], there is a large heterogeneity in the remodeling response after an infarction.…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…These include the use of erythropoietin, adenosine, hydrogen sulfide, and intracoronary KAI-9803, an inhibitor of protein kinase delta. 15,16 If any of these turn out to be more beneficial than HBO, they may be more practical to administer.…”
Section: Ischemic Reperfusion Injurymentioning
confidence: 99%